Engineering copolymeric artificial cornea with salt porogen. Issue 6 (29th June 2013) - Zellander, Amelia; Wardlow, Melissa; Djalilian, Ali; Zhao, Chenlin; Abiade, Jeremiah; Cho, Michael
Abstract Artificial corneas or keratoprostheses (KPros) are designed to replace diseased or damaged cornea. Although many synthetic KPros have been developed, current products are often inappropriate or inadequate for long term use due to ineffective host integration. This study presents an alternative approach of engineering a KPro that comprises a combination of poly (2‐hydroxyethyl methacrylate) (PHEMA), poly (methyl methacrylate) (PMMA), and sodium chloride (NaCl) as porogen. Based on the core‐skirt model for KPro, the porous outer portion of artificial cornea (skirt) was engineered by combining NaCl with HEMA and MMA monomers to promote tissue ingrowth from the host. The central optic (core) was designed to provide >85% light transmission in the visible wavelength range and securely attached to the skirt. Mechanical tensile data indicated that our KPro (referred to as salt porogen KPro) is mechanically stable to maintain its structure in the ocular environment and during implantation. Using human corneal fibroblasts (HCFs), we demonstrate that the cells grew into the pores of the skirt and proliferated, suggesting biointegration is adequately achieved. This novel PHEMA‐PMMA copolymeric salt porogen KPro may offer a cornea replacement option that leads to minimal risk of corneal melting by permitting sufficient tissue ingrowth and mass transport. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 1799–1808, 2014.